Designing Web-Based Materials for Descriptive Writing at The Tenth Grade Level - Putrisabila Fitalia; Alimin; Happy Kusuma Wardani (PROJECT (Professional Journal of English Education), 2026)
This research aims to develop web-based materials for teaching writing of descriptive text. This research uses the ADDIE Model of research and development (R&D). The subjects of this research were 36 students in class X-6 at SMAN 1 Dukun. The needs analysis stage involve analyzing the needs for web- based materials. The design stage consist of arranging learning objectives, model texts, grammar support, interactive exercises, and writing activities. The development stage involve validating the learning media by several experts and English teachers. The implementation stage involve implementing the web-based materials to engage student response to the learning media. Finally, the evaluation stage show that the results of the learning media development, specifically the web-based materials were positively received, showing that the media was suitable for use and was able to motivate students in web-based teaching of writing descriptive texts.